Atomic structure and chemistry of a[100] dislocation cores in La2/3Sr1/3MnO3 films. (May 2017) - Song, Kepeng; Du, Kui; Ye, Hengqiang
Graphical abstract: Highlights: Nonstoichiometric dislocation cores with oxygen vacancies in LSMO films were quantitatively characterized. MnLa antisite defects at dislocation cores were discovered. The special configuration of the dislocation core was proposed to result from the strain accommodation. Abstract: Oxide thin films with perovskite structures possess multifunctional properties, while defects in the films usually have significant influences on their physical properties. Here, the atomic structure and chemistry ofa [100] dislocation cores in epitaxial La2/3 Sr1/3 MnO3 films were investigated by aberration-corrected scanning transmission electron microscopy combining with atomically resolved electron energy-loss spectroscopy imaging. The results demonstrated an edge dislocation terminated with Mn columns and significant nonstoichiometry at the dislocation core region. Quantitative analysis using core-loss spectrum indicates that La/Mn and O/Mn ratios are decreased at the dislocation core. Antisite defects with Mn ions at La-sites were directly determined at the dislocation cores with electron energy-loss spectroscopy. The structure of the dislocation core is discussed on the basis of high-angle annular dark-field imaging and electron energy loss spectroscopy results.